2008
DOI: 10.1111/j.1600-079x.2008.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates calcium homeostasis in myocardial and ischemia–reperfusion injury in chronically hypoxic rats

Abstract: Chronic hypoxia (CH) leads to the deterioration of myocardial functions with impaired calcium handling in the sarcoplasmic reticulum (SR), which may be mediated by oxidative stress. We hypothesized that administration of antioxidant melatonin would protect against cardiac and ischemia-reperfusion (I/R) injury by ameliorating SR calcium handling. Adult Sprague-Dawley rats that had received a daily injection of melatonin or vehicle were exposed to 10% oxygen for 4 wk. The heart of each rat was then dissected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 69 publications
5
41
0
Order By: Relevance
“…Although it is not a direct measurement of oxidative stress, we found an increased MDA level in the adrenal medulla of hypoxic rats, suggesting elevated levels of lipid peroxidation, which could be mediated by CIH-induced oxidative stress. This is consistent with our previous studies reporting antioxidant melatonin attenuated the elevated MDA levels and cellular injuries induced by CIH-induced lipid peroxidation [7,8]. Also, our results showed the increased level of NTR-immunoreactivity in the adrenal medulla of CIH rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although it is not a direct measurement of oxidative stress, we found an increased MDA level in the adrenal medulla of hypoxic rats, suggesting elevated levels of lipid peroxidation, which could be mediated by CIH-induced oxidative stress. This is consistent with our previous studies reporting antioxidant melatonin attenuated the elevated MDA levels and cellular injuries induced by CIH-induced lipid peroxidation [7,8]. Also, our results showed the increased level of NTR-immunoreactivity in the adrenal medulla of CIH rats.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have also shown that recurrent episodes of apnea/hypopnea cause chronic intermittent hypoxia (CIH), which induces lipid peroxidation and subsequently causes the pathophysiological change in the OSA patient [4,5,6]. Indeed, we have shown that CIH-induced lipid peroxidation plays a significant pathogenic role in the hippocampal injury in a rat model with chronic exposure to intermittent hypoxia mimicking a severe OSA condition, which underpins the involvement of overproduction of reactive oxygen species (ROS) and free radicals in apoptotic cell death and neuronal dysfunction [7,8]. In addition, it has been shown that that cellular injuries caused by lipid peroxidation lead to inflammation, which induces the inflammatory response that could be an important contributing factor in promoting cardiovascular morbidity in OSA patients [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In another research study by Yeung et al (2008), the effects of chronic hypoxia (10% oxygen for 28 days) on myocardial functions were investigated in isolated perfused rat hearts. They reported that the ratio of heart-to-body weight was increased in the chronically hypoxic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiologically, the heart also benefits from melatonin [49]. Yeung et al [50] suggested that melatonin is cardioprotective against chronic hypoxia-induced myocardial injury because it improves calcium handling in the sarcoplasmic reticulum (SR) of cardiomyocytes via an antioxidant mechanism. Furthermore, Genade et al [51] showed that melatonin-induced cardioprotection may be receptor dependent and that its anti-adrenergic actions, mediated by NOS and guanylyl cyclase activation, are important contributors to its ability to forestall molecular damage in the cardiomyocyte due to IR.…”
Section: Cell Biological Actions Of Melatonin In the Cardiomyocytementioning
confidence: 99%